PREGNANCY EXERCISES AND DELIVERY PROCESS IN MOTHERS GIVING BIRTH AT SUMOWONO HEALTH CENTER SEMARANG REGENCY - Dwi Okta Diarini; Yuliaji Siswanto; Heni Hirawati Pranoto; Ima Syamrotul; Wulan Margiana; Hamdiah Hamdiah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Pregnancy exercise is a therapy to prepare pregnant women either physically or mentally, so that the delivery can take place spontaneously. The delivery process is a process of releasing the fetus from the uterus to the outside of the uterus through the birth canal. This study aimed to find the correlation between pregnancy exercises and delivery process in mothers giving birth. Method: This was a descriptive-correlative study with cross sectional approach. The data sampling used purposive sampling technique. The population in this study was all mothers who attended the pregnancy exercises in period from January to December 2014 in the region of Sumowono Health Center Semarang Regency. The samples were 132 respondents. The data analysis used Chi Square test. Results: The results of this study indicated that the mothers who attended the pregnancy exercises regularly and had spontaneous delivery were 88.2%. While the mothers who attended the pregnancy exercises regularly and did not have spontaneous delivery were 56.4%. Based on the Chi Square test obtained p-value of 0.000 < α (0.05) so that it could be concluded that there was a significant correlation between pregnancy exercises and delivery process in mothers giving birth at Sumowono Health Center Semarang Regency. Conclusion: It shows that by implementing pregnancy exercises on a regular basis can help the delivery process. Therefore, every pregnant woman is expected to attend and participate in the pregnancy class in their neighborhood.